1980
DOI: 10.2466/pms.1980.51.2.403
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Memory for Kinesthetic Movement Information: Influence of Location Cues on Recall of Distance

Abstract: To isolate location and distance cues a two-dimensional movement task was given to 32 college students. Reliability of location cues was varied; a criterion distance was recalled accurately with and without location cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Usually, these kinds of tasks are a combination of the perception of distance and position [1], [2], [3], [4]. In general, reproducing a position yields a movement ending closer to the physical location than reproducing a distance [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, these kinds of tasks are a combination of the perception of distance and position [1], [2], [3], [4]. In general, reproducing a position yields a movement ending closer to the physical location than reproducing a distance [5], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even though most of the motor learning literature supports the salience of the cue of location, Schwartz points out that Ashby, Shea, and Howard (1980) found that the ". .. amplitude of movement or distance traveled by a limb can be recalled accurately without the availability of information concerning location.…”
mentioning
confidence: 95%